2020
DOI: 10.3390/molecules25071523
|View full text |Cite
|
Sign up to set email alerts
|

Full Parametric Study of the Influence of Ionomer Content, Catalyst Loading and Catalyst Type on Oxygen and Ion Transport in PEM Fuel Cell Catalyst Layers

Abstract: To advance the technology of polymer electrolyte membrane fuel cells, material development is at the forefront of research. This is especially true for membrane electrode assembly, where the structuring of its various layers has proven to be directly linked to performance increase. In this study, we investigate the influence of the various ingredients in the cathode catalyst layer, such as ionomer content, catalyst loading and catalyst type, on the oxygen and ion transport using a full parametric analysis. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…Nafion acts as a strong adhesive to introduce a mechanical stability to the catalytic layer, however, the ionomer distribution is a known issue in fuel cell research due to its influence on local reactant transportation and associated mass (oxygen) transport resistances. 38,39 Likewise, the transport of reactants in CO 2 RR towards the active sites should also be sensitive to the local distribution of the ionomer, acting as a barrier for the CO 2 and HCO 3 À transport.…”
Section: Cathode Electrode Design and Architecturementioning
confidence: 99%
“…Nafion acts as a strong adhesive to introduce a mechanical stability to the catalytic layer, however, the ionomer distribution is a known issue in fuel cell research due to its influence on local reactant transportation and associated mass (oxygen) transport resistances. 38,39 Likewise, the transport of reactants in CO 2 RR towards the active sites should also be sensitive to the local distribution of the ionomer, acting as a barrier for the CO 2 and HCO 3 À transport.…”
Section: Cathode Electrode Design and Architecturementioning
confidence: 99%
“…Indeed, carbon treatment methods to tune the PFSA/carbon interaction have been successfully employed to control CL performance. [53][54] Similarly, one metric often reported is the ionomer-to-carbon (I/C) ratio, where optimal ratios [55][56][57][58][59][60][61] seem dependent on carbon type; given the results herein, ideal ratios will also likely vary with solvent and EW. Additional Parameters.…”
mentioning
confidence: 91%
“…Therefore, given the larger surface area of carbon relative to platinum in most electrocatalyst particles, PFSA/particle adsorption (and subsequent aggregation) in inks is likely dominated by the PFSA/carbon interaction. Indeed, carbon treatment methods to tune the PFSA/carbon interaction have been successfully employed to control CL performance. , Similarly, one metric often reported is the ionomer-to-carbon (I/C) ratio, where optimal ratios seem dependent on carbon type; given the results herein, ideal ratios will also likely vary with solvent and EW.…”
mentioning
confidence: 92%
“…In the present work, it is assumed that ionomer content cannot change the CL thickness, which has been confirmed in Ref.. 12 As a result, the CCL porosity decreases gradually towards the MEM/CCL interface due to the gradient reduction of ionomer content along the reverse direction. 13,14 Additionally, the change of ionomer content also affects the thickness of ionomer film coating the agglomerate.…”
Section: Effect Of Ionomer-gradient Distributionmentioning
confidence: 99%
“…In recent years, the design of the spatial distribution of ionomer in CCL has become a valuable selection to optimize the CCL structure. 9,[12][13][14][15][16] Alink et al 12 experimentally studied a full parametric study of various catalyst layer compositions. It was found that the optimum ionomer content is dependent on the operating load and gas relative humidity (RH).…”
Section: Introductionmentioning
confidence: 99%